2020
DOI: 10.3389/fphys.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Attenuates Diabetic Nephropathy by Promoting Autophagy in Podocytes

Abstract: Puerarin, an active compound of radix puerariae, is a major compound used in Chinese herbal medicines to treat patients with diabetic nephropathy (DN). In the previous studies, we showed that puerarin exerts renoprotective effects in Streptozocin (STZ)induced diabetic mice through activation of Sirt1 and anti-oxidative effects. Here, we further investigated the underlying mechanism mediating the renal protective effects of puerarin in DN. We studied the effects and mechanism of puerarin in STZ-induced diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Since evidence shows that the AMPK signaling pathway regulates autophagy [ 25 , 26 ], we aimed to determine whether miR-199a-5p mediates autophagy by regulating that pathway. It has also been reported that Sirt1 can affect AMPK activation to mediate autophagy [ 27 , 28 ]. First, we sought to identify a potential binding sequence for miR-199a-5p within the sequence of Sirt1 using TargetScan ( http://www.targetscan.org/ ).…”
Section: Resultsmentioning
confidence: 99%
“…Since evidence shows that the AMPK signaling pathway regulates autophagy [ 25 , 26 ], we aimed to determine whether miR-199a-5p mediates autophagy by regulating that pathway. It has also been reported that Sirt1 can affect AMPK activation to mediate autophagy [ 27 , 28 ]. First, we sought to identify a potential binding sequence for miR-199a-5p within the sequence of Sirt1 using TargetScan ( http://www.targetscan.org/ ).…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is also involved in the maintenance of podocyte function and cell homeostasis ( 22 ). To define the AGF-induced alterations in autophagy, the expression levels of autophagy biomarkers (LC3II/I and Beclin-1) were evaluated by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Hemin could also exert protective functions on endothelium through synthesis of bilirubin, as proposed in the db/db genetic mouse model of diabetes where hemin and bilirubin were reportedly enhanced, similar to the endothelium-mediated relaxation of aortas [ 189 ]. Several other HO-1 inducers, namely, sinapic acid [ 199 ], artemisin [ 200 ] and puerarin [ 201 ], reportedly reduced kidney injuries in STZ-treated rodents, offering up the possibility of new therapeutic approaches.…”
Section: Ho-1 In Kidney Diseasesmentioning
confidence: 99%